Impacts of Macroeconomic Factors on Banking Stocks Performance: An Empirical Study on UK Banking Industry - Ma, Ke (2011)
This paper examines the effect of macroeconomic factors, i.e. inflation rate, interest rate, and exchange rate, on the UK banking industry stock returns. The simple and straightforward multiple regression model is employed to estimate the multi-factor influence. Before the model estimation, stationary test, autocorrelation test, heterscedasticity test as well as multicollinearity test are performed to ensure the reliability of data. Our result shows that all of these three factors have a positive relation with banking stock returns, although some unique characteristics of each individual factor are also identified.